Nutritional status of patients with gastrointestinal cancer receiving care in a public hospital, 2010-2011 - Prado, Corina Dias do [UNESP]; Duarte Bonini Campos, Juliana Alvares [UNESP] (Aula Médica Ediciones, 2013)
Objective: To identify the nutritional status of patients with gastrointestinal cancer and verify its association with demographic and clinical characteristics.Methods: This was a cross-sectional study with a nonprobability sampling design. The participants were 143 adult patients with gastrointestinal cancer, receiving care in the Amaral Carvalho Hospital (Jau-SP, Brazil) from November 2010 to October 2011. A survey was conducted to collect information for the purpose of demographic and clinical characterization. In order to identify nutritional status, the Scored Pati2) test were used. The prevalence ratio (PR) was estimated. The level of significance adopted was 5%.Results: The mean age of patients was 57.45 (SD = 9.62) years, with Stages HI and IV of the disease being the most prevalent (39.2% and 35.0%). There was 44.8% prevalence of malnutrition. The undernourished individual more frequently reported having problems with eating (pcent-Generated Subjective Global Assessment (Scored PG-SGA) was applied. Descriptive statistics and the Chi-square (< 0.001), presented less desire to eat (p < 0.001), more nausea (p = 0.001), vomiting (p = 0.006), constipation (p < 0.001) and pain (p < 0.001) than eutrophic patients, and more frequently related feeling nauseated by the smell of food (p = 0.012), difficulty with swallowing (p = 0,002) and early satiety (p = 0.020). As regards the prevalence ratio, greater chance was observed of malnourished individuals being exposed to a larger portion of the symptoms related in the Scored PG-SGA.Conclusion: High prevalence of malnutrition was observed among patients with gastrointestinal cancer, with significant association with clinical symptoms directly related to the eating process. (Nutr Hosp. 2013;28:405-411) DOI:10.3305/nh.2013.28.2.6305
Keywords: Nutritional assessment; Gastrointestinal neoplasms; Drug therapy; Neoplasm staging